Effectiveness of a mobile medical van in providing screening services for STDs and HIV. - Liebman, Jon; Pat Lamberti, Mary; Altice, Frederick (Public health nursing (Boston, Mass.), 2002)
This retrospective study assesses the efficacy of a mobile medical van in screening high risk individuals and identifying new cases of HIV and other sexually transmitted diseases (STDs) in an urban setting from July 1996 through March 1997. High risk sex and drug use were common, while consistent condom use was rare. Relatively few patients were screened for STDs; positive cases represented only a small proportion of the STD cases identified in the study community. The mobile program, however, accounted for 11.5% of all HIV tests conducted at public test sites in the city. Mobile medical programs have the potential to improve STD and HIV control efforts by providing services to high risk individuals who may lack access to care elsewhere. Doing so, however, will require more active case finding techniques, including new, less invasive techniques to test asymptomatic individuals.
Keywords: Adolescent; Adult; Connecticut; Female; HIV Infections; Humans; Male; Mass Screening; Mobile Health Units; Program Evaluation; Retrospective Studies; Risk Factors; Sexually Transmitted Diseases